SARS-CoV-2 vaccination responses in untreated, conventionally treated and anticytokine-treated patients with immune-mediated inflammatory diseases. Issue 10 (6th May 2021) - Simon, David; Tascilar, Koray; Fagni, Filippo; Krönke, Gerhard; Kleyer, Arnd; Meder, Christine; Atreya, Raja; Leppkes, Moritz; Kremer, Andreas E; Ramming, Andreas; Pachowsky, Milena L; Schuch, Florian; et al.
Abstract : Objectives: To better understand the factors that influence the humoral immune response to vaccination against SARS-CoV-2 in patients with immune-mediated inflammatory diseases (IMIDs). Methods: Patients and controls from a large COVID-19 study, with (1) no previous history of COVID-19, (2) negative baseline anti-SARS-CoV-2 IgG test and (3) SARS-CoV-2 vaccination at least 10 days before serum collection were measured for anti-SARS-CoV-2 IgG. Demographic, disease-specific and vaccination-specific data were recorded. Results: Vaccination responses from 84 patients with IMID and 182 controls were analysed. While all controls developed anti-SARS-CoV-2 IgG, five patients with IMID failed to develop a response (p=0.003). Moreover, 99.5% of controls but only 90.5% of patients with IMID developed neutralising antibody activity (p=0.0008). Overall responses were delayed and reduced in patients (mean (SD): 6.47 (3.14)) compared with controls (9.36 (1.85); p<0.001). Estimated marginal means (95% CI) adjusted for age, sex and time from first vaccination to sampling were 8.48 (8.12–8.85) for controls and 6.90 (6.45–7.35) for IMIDs. Significantly reduced vaccination responses pertained to untreated, conventionally and anticytokine treated patients with IMID. Conclusions: Immune responses against the SARS-CoV-2 are delayed and reduced in patients with IMID. This effect is based on the disease itself rather than concomitant treatment.